Developing an e-Learning using interactive multimedia approach : the basic French language / Anisah Anuar - Anuar, Anisah (2005)
Electronic learning (e-learning) root is a combination of computer science and education field. It is a learning method, which is learning using an electronic media. E-leaming actually is a system that allows user to leam anywhere and anytime, as long as the user has a proper configured computer. E-learning can be CD-ROM based, network-based, internet-based or intranet-based. Nowadays, the traditional learning is still used. There are various common problems is a leaming environment. Class environment, class size, teacher's attitude, student's attitude and insufficient learning tools, all these can affect the process of teaching and leaming. Often found that, some students forget whatever had been taught in class. It is because they do not fully attention in class. In some case. Student takes time to master certain part of topic. Every student has different level of performance and ability to accept a subject. Moving too slowly can lead a sense of boredom to student, whereas progress too quickly can leave the less able students with the feeling of inadequacy. Both of these situations can cause frustration and tendency to impede the leaming process. The purpose of developing this project is to give the opportunity for user to learn independently when deemed necessary on their own rate. The scope of this project is to allow any Internet user who wants to study simple and daily speech of French language. These projects develop a prototype for basic French language package that provide e-dictionary in order for user searching (translation and meaning for each word). Basically, the approaches that have been applied are combination of text, graphic, animation, audio and interactivity element